EFEKTIVITAS ETIKA PARIWARA INDONESIA (EPI) DALAM MENGATUR IKLAN DI ERA DIGITAL: ANALISIS KESENJANGAN ANTARA REGULASI DAN PRAKTIK - Ilyasa, Ilyasa Nur Ilham; Dinnary Athena, Dhavina; Anjani, Anjani Putri Ramadhani; Irvingia, Irvingia Agya Anandya; Daniel, Daniel Handoko (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the effectiveness of the Indonesian Advertising Ethics (EPI) in regulating advertisements in the digital era, based on the gap between regulations and practice in the field. The research utilizes a qualitative approach, employing documentary studies and in-depth interviews to gain a comprehensive understanding of the issue. The results show that the EPI's effectiveness in maintaining fairness, honesty, and responsibility in digital advertising is still weak. This weakness is not due to the substance of the EPI itself, but mainly because of the rapid development of technology, the vast expansion of digital media, low compliance from practitioners, and the self-regulatory approach that relies on the awareness and responsibility of each actor. The study also finds a gap between regulation and practice due to the EPI’s continued use of a framework designed for traditional media, making it less adaptable to digital media's unique challenges. Therefore, the research concludes that a more adaptive, collaborative, and multi-stakeholder approach is required to safeguard advertising ethics and protect the public's interest in the digital era